Torque sensor based electrically assisted hybrid rickshaw-van with PV assistance and solar battery charging station - Khan, Fabiha Roshni; Aurony, Anika Tasnim; Rahman, Ataur; Munira, Faiza; Halim, Nazia; Azad, AKM Abdul Malek (© 2015 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 3rd International Conference on Advances in Electrical Engineering, ICAEE 2015; Independent UniversityDhaka; Bangladesh; 17 December 2015 through 19 December 2015 [© 2015 Institute of Electrical and Electronics Engineers Inc.] The conference paper's definite version is available at: http://10.1109/ICAEE.2015.7506851